Women in Climate Change for Sustainable Impact: Ecotourism for Poverty Alleviation in Rural Akwa Ibom State - A. M. Imikan; C. I. Oseghale; I. C. Nda; A. E. Udo; N. C. Ekong (RIRAI Publisher, 2023)
This study sought to assess the contributions of ecotourism as poverty alleviation strategy amongst women in rural Akwa Ibom State. The study was descriptive in nature and employed survey research design. Based on reconnaissance survey, three major ecotourism sites were purposively selected for the study, one from each of the senatorial districts in Akwa Ibom State, making a sample size of three (3). Fifty questionnaire forms were administered in each study site using simple random sampling method and same were returned. This makes a total of one hundred and fifty (150) questionnaire forms. Data were analysed descriptively based on the questionnaire responses. Furthermore, to evaluate the impact of women on sustainable ecotourism development, chi-square (x²) statistical method was employed for the hypothesis test. The result shows that women have significant impacts on sustainable ecotourism development. This indicates that women are the integral part of development. Also, new ecotourism attraction sites were discovered during the inventory. Therefore, the researcher recommends that women should actively participate and involve in ecotourism related activities. They should reinforce positive conservation habit towards natural resource base. Also, biodiversity should be advocated and women should be integrated in planning and decision making towards tourism development since they are more vulnerable.